PENERAPAN PSAK 116 (IFRS 16) DALAM INDUSTRI TRANSPORTASI DAN LOGISTIK DI INDONESIA: DAPATKAH MENINGKATKAN KEANDALAN INFORMASI LAPORAN KEUANGAN BAGI PEMEGANG SAHAM? - Didi Didi; Muhammad Nur Afif; Hendri Alfarisi; Agus Sumarna (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research aims to prove whether the application of PSAK 116 on Leases can increase the reliability of financial report information for shareholders in making economic decisions. The population of this research is issuers in the Transportation and Logistics Industry Sub-Sector listed on the Bursa Efek Indonesia (BEI) for 7 years (2016-2022), totaling 37 companies. The sampling technique uses a purposive sampling technique so that from a population of 37, 14 companies can be sampled. Thus, the research used 98 observational data collected in a time series. The data analysis technique uses Panel Data Multiple Regression with the help of the EViews 12 Full Version statistical tool. The research results found evidence that Return On Assets (ROA) does not have a direct effect on company value but has an effect after being moderated by the application of PSAK 116 on Leases